2009
DOI: 10.1007/s10964-009-9452-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Distortion in the Relationship Between Abuse, Assault, and Non-Suicidal Self-Injury

Abstract: The purpose of this study was to examine the relationship between childhood abuse, assault, cognitive distortion, and non-suicidal self-injury (NSSI) in a clinical adolescent sample. The sample included one hundred eighty-five psychiatrically hospitalized adolescents and their parents. Adolescent participants were predominantly female (71.4%), Caucasian (84%), and of non-Hispanic ethnicity (9.2%). Participants completed a diagnostic interview and self-report measures to assess youth history of abuse and assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 36 publications
2
27
1
1
Order By: Relevance
“…The methods used in this study have been described in a prior publication (Weismoore & Esposito-Smythers, 2010). Participants were 185 adolescents (ages 13 to 18) recruited from a psychiatric inpatient facility in the northeastern United States.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in this study have been described in a prior publication (Weismoore & Esposito-Smythers, 2010). Participants were 185 adolescents (ages 13 to 18) recruited from a psychiatric inpatient facility in the northeastern United States.…”
Section: Methodsmentioning
confidence: 99%
“…The phenomenon of non-suicidal self-injury (NSSI), which is generally defined as "the direct, deliberate destruction of one's own body tissue in the absence of suicidal intent" (Nock & Favazza, 2009, p. 9), is now recognized globally as a major public health issue, with up to 70% of children and adolescents with mental health problems engaging in NSSI (Kaess et al, 2013;Thomassin, Shaffer, Madden, & Londi, 2016;Weismoore & Esposito-Smythers, 2010;Zetterqvist, Lundh, & Svedin, 2014). Historically, NSSI has been…”
Section: Introductionmentioning
confidence: 99%
“…Various studies from Asia (You and Leung, 2012), Australia (Tanner et al, 2015), Canada (Armiento et al, 2014), Europe , and the US (Sornberger et al, 2012;Brausch and Gutierrez, 2010) have found lifetime prevalence rates of NSSI among adolescent students ranges between 10-32%. Higher rates have been reported among adolescents from clinical settings ranging from 24% in Canada (Armiento et al, 2016), to 40% in Europe (Kaess et al, 2013), and 63-80% in the US (Auerbach et al, 2014;Victor et al, 2012;Weismoore and Esposito-Smythers, 2010). Swannell et al (2014) conducted a systematic review of published studies on NSSI across the globe and found a pooled lifetime prevalence estimate of NSSI among adolescents to be 17.2%.…”
Section: Introductionmentioning
confidence: 99%